Circulating exosomes decrease in size and increase in number between birth and age 7: relations to fetal growth and liver fat - Díaz, Marta; Casano, Paula; Quesada, Tania; López-Bermejo, Abel; de Zegher, Francis; Villarroya, Francesc; Ibáñez, Lourdes (Frontiers in Endocrinology, 2023)
Purpose Exosomes play a key role in cell-to-cell communication by transferring their cargo to target tissues. Little is known on the course of exosome size and number in infants and children. Methods Longitudinally, we assessed the size and number of circulating exosomes at birth and at ages 2 and 7 yr in 75 infants/children born appropriate-for-gestational-age (AGA; n=40) or small-for-gestational-age (SGA; n=35 with spontaneous catch-up), and related those results to concomitantly assessed measures of endocrine-metabolic health (HOMA-IR; IGF-1), body composition (by DXA at ages 0 and 2) and abdominal fat partitioning (subcutaneous, visceral and hepatic fat by MRI at age 7). Results Circulating exosomes of AGAs decreased in size (on average by 4.2%) and increased in number (on average by 77%) between birth and age 7. Circulating exosomes of SGAs (as compared to those of AGAs) had a larger size at birth [146.8 vs 137.8 nm, respectively; p=0.02], and were in lower number at ages 2 [4.3x1011vs 5.6x1011 particles/mL, respectively; p=0.01] and 7 [6.3x1011vs 6.8x1011 particles/mL, respectively; p=0.006]. Longitudinal changes were thus more pronounced in SGAs for exosome size, and in AGAs for exosome number. At age 7, exosome size associated (P<0.0001) to liver fat in the whole study population. Conclusion Early-life changes in circulating exosomes include a minor decrease in size and a major increase in number, and these changes may be influenced by fetal growth. Exosome size may become one of the first circulating markers of liver fat in childhood.